Melflufen: A Peptide–Drug Conjugate for the Treatment of Multiple Myeloma - Mateos, María-Victoria (J Clin Med, 2020)
Despite the availability of new therapies that have led to improved outcomes for patients with multiple myeloma, most patients will eventually relapse. With triplet and even quadruplet combination therapies becoming standard in the first and second line, many patients will have few treatment options after second-line treatment. Melflufen (melphalan flufenamide) is a first-in-class peptide–drug conjugate (PDC) that targets aminopeptidases and rapidly releases alkylating agents into tumor cells. Once inside the tumor cells, melflufen is hydrolyzed by peptidases to release alkylator molecules, which become entrapped. Melflufen showed anti-myeloma activity in myeloma cells that were resistant to bortezomib and the alkylator melphalan. In early phase studies (O-12-M1 and HORIZON [OP-106]), melflufen plus dexamethasone has demonstrated encouraging clinical activity and a manageable safety profile in heavily pretreated patients with relapsed/refractory multiple myeloma, including those with triple-class refractory disease and extramedullary disease. The Phase III OCEAN study (OP-104) is further evaluating melflufen plus dexamethasone in patients with relapsed/refractory multiple myeloma. The safety profile of melflufen is characterized primarily by clinically manageable hematologic adverse events. Melflufen, with its novel mechanism of action, has the potential to provide clinically meaningful benefits to patients with relapsed/refractory multiple myeloma, including those with high unmet needs.